A self-organized location aware energy efficient protocol for wireless sensor networks. (January 2015) - Santhi, C.; Sharmila, D.
Abstract: Wireless Sensor Networks (WSNs) are self-organized distributed networks composed of a large quantity of energy-limited nodes. WSN constraints are well known; minimum energy consumption, localization and self-organization. To solve these issues separately, more transmission power is required. To overcome this problem, a combined protocol titled SLEEP (Self-organized Location aware Energy Efficient Protocol) is proposed in this work. The protocol creation is divided into four phases: (1) localization aware structure; (2) topology control; (3) energy efficient model and (4) self-organization in SLEEP. The simulation results showed that the proposed work performed well in terms of energy efficiency and quality of service (QoS) parameters like packet delivery ratio.